Gold-catalyzed nucleophilic tandem cyclizations of tetraethynylethene derivatives. Issue 35 (2nd September 2015) - Schädlich, Johannes; Wieteck, Marcel; Rudolph, Matthias; Larsen, Mie Højer; Hashmi, A. Stephen K.
Abstract: Symmetric and non-symmetric tetraethynylethene derivatives possessing nucleophilic groups were synthesized and subjected to gold catalysts. By a fourfold nucleophilic tandem cyclization extended π-systems like carbazolocarbazoles are accessible in high efficiency and in complete atom economy. Graphical abstract: